2013
DOI: 10.1161/atvbaha.112.301009
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Fat and Associations With Metabolic Risk Factors in the Framingham Heart Study

Abstract: Objective Intramuscular fat accumulates between muscle fibers or within muscle cells. We investigated the association of intramuscular fat with other ectopic fat deposits and metabolic risk factors. Approach and Results Participants (n = 2945; 50.2% women; mean age 50.8 years) from the Framingham Heart Study underwent multidetector computed tomography scanning of the abdomen. Regions of interest were placed on the left and right paraspinous muscle and the muscle attenuation (MA) in Hounsfield units were aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 35 publications
2
97
0
Order By: Relevance
“…26,27 Results from the Framingham study have also suggested that people with higher BP also have higher levels of TC. 28 In the present study, multivariate analysis showed that participants with either high TC, low HDL-C, high LDL-C, or high TG were more likely associated with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Results from the Framingham study have also suggested that people with higher BP also have higher levels of TC. 28 In the present study, multivariate analysis showed that participants with either high TC, low HDL-C, high LDL-C, or high TG were more likely associated with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RA patients may have reduced muscle strength due to greater intramuscular fat infiltration, which is indicated by decreased muscle density on peripheral quantitative computed tomography (QCT) scans. Studies in a large community-based cohort demonstrated that greater fat indices were associated with greater intramuscular fat infiltration (12,13). One should also recognize that the association between muscle outcomes and adiposity might be altered in a disease state characterized by inflammatory cachexia such as RA.…”
Section: Introductionmentioning
confidence: 99%
“…None of the associations, however, persisted after correction for BMI and visceral adipose tissue. In men, there remained an association between muscle attenuation and lipid levels and in women, an association between muscle attenuation and metabolic syndrome remained 13 .…”
Section: Tracking Obesity and Its Consequences From Birth To Adulthoomentioning
confidence: 99%
“…Goodpaster used that measure to test the relationship of muscle content to strength in older subjects. In recently reported studies by Therkelsen and colleagues in ATVB , the relationship between muscle attenuation coefficient with metabolic risk factors and additionally adjusted for BMI and visceral adipose tissue was addressed in subjects of the Framingham Heart Study 13 . The authors showed that in both men and women, muscle attenuation was associated with dysglycemia, dyslipidemia and hypertension.…”
Section: Tracking Obesity and Its Consequences From Birth To Adulthoomentioning
confidence: 99%